Radicalism and terrorism in the 21st century : implications for security - Sroka, Anna (Political scientist); Castro-Rial Garrone, Fanny; Torres Kumbrián, Rubén Darío (Studies in politics, security and society., 2016)
This book addresses the issues of radicalism and terrorism. Each of the two phenomena are analyzed from a multidisciplinary perspective. The book contains articles which explore legal, political, psychological, economic and social aspects of radicalism and terrorism.